Efficiency of Sodium Polyacrylate to Improve Durability of Concrete under Adverse Curing Condition. (28th December 2015) - Manzur, Tanvir; Iffat, Shohana; Noor, Munaz Ahmed
Abstract : The conventional external curing process requires supply of large amount of water in addition to mixing water as well as strict quality control protocol. However, in a developing country like Bangladesh, many local contractors do not have awareness and required knowledge on importance of curing which often results in weaker concrete with durability issues. Moreover, at times it is difficult to maintain proper external curing process due to nonavailability of water and skilled laborer. Internal curing can be adopted under such scenario since this method is simple and less quality intensive. Usually, naturally occurring porous light weight aggregates (LWA) are used as internal curing agent. However, naturally occurring LWA are not available in many countries like Bangladesh. Under these circumstances, Super Absorbent Polymer (SAP) can be utilized as an alternative internal curing agent. In this study, sodium polyacrylate (SP) as SAP has been used to produce internally cured concrete. Desorption isotherm of SP has been developed to investigate its effectiveness as internal curing agent. Test results showed that internally cured concrete with SP performed better in terms of both strength and durability as compared to control samples when subjected to adverse curing conditions where supply of additional water for external curing was absent.